Social Media Use in Primary and Secondary Education Institutions as a Communication Tool in the Framework of School Culture - Berna Kesim; Ramazan Alabaş (Uluslararası Türk Eğitim Bilimleri Dergisi)
The schools, as social institutions, form a unique school culture with their characteristics, shared values, and beliefs. The social foundations of education are closely related to the environment. One of the factors affecting school culture is communication with its environment as the school interacts with its environment. Schools realize institutional communication, which has an important place in their culture, through different tools. This study aims to determine the use of social media tools as a communication tool in primary and secondary education institutions within the framework of school culture. In the study, the use of social media tools in educational institutions was revealed in line with the opinions of school social media managers. Conducted with a case study approach by qualitative research methodology, the study group of the research was determined by maximum diversity sampling from purposeful sampling methods. The interviews were conducted with the participation of 18 school social media managers working in public schools at different levels and with different socioeconomic levels in Istanbul. Social media managers are teachers, and 15 of these teachers also have administrative duties (1 is a school principal, and 14 are vice principals) in the same school. The data were collected through a semi-structured interview form and analyzed using a content analysis approach. The results of the study revealed that schools prefer Instagram more frequently and that school social media managers use their social media accounts for sharing information and news and promoting the school. The ethical principles followed by schools in social media administration were collected in the categories of respecting personal rights and private life, sharing content related to the institution, compliance with the legislation, the posts reflecting the values, being shared with the decision of the commission, using Turkish correctly, and student and parent satisfaction. The participants stated that they strive to establish two-way communication with their followers in their social media accounts and that social media contributes to their organizations more frequently in terms of usefulness, advertising and promotion, and stakeholder satisfaction.